Conceptual study of mobile retailing acceptance among Malaysian women - Azlina Bujang; Norbayah Mohd Suki; Norazah Mohd Suki (American Scientific Publishers, 2017)
Two fastest growing technologies like the internet and mobile technology have driven a revolution in mobile retailing sectors. Mobility and flexibility become a demand nowadays since people prefer to have retailing concept (anytime and anywhere). This conceptual paper aimed to study on the discovery of factors on women’s acceptance, which contributes to successful mobile retailing among women in Malaysia. Secondly, it aimed to access the extent of information, regarding the mobile retailing sectors, based on previous documented literature. This research sheds light on the body of knowledge, ultimately by looking at women’s acceptance of mobile retail industry in Malaysia. It entails optimism perception as this study has broaden up strategies as well as the new business market for retailers that embark into the mobile retailing sector, by attracting more women consumers to use mobile retailing as a way to do online shopping.